Methods for pre-treatment of waste batteries
Through the discharge reaction of graphite and activated carbon mixture with sodium chloride solution and activated carbon regeneration technology, the problems of water pollution and high energy consumption in discharge treatment of waste batteries and electrolyte recovery are solved, and efficient and green battery pretreatment and electrolyte are achieved. Recycling, suitable for large-scale applications.
Patent Information
- Application Number
- CN202011187081.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-10-29
AI Technical Summary
The discharge treatment and electrolyte recovery methods of waste batteries in the prior art have problems of water pollution and high energy consumption, and the equipment is complex and difficult to widely use.
Graphite and activated carbon are used to prepare a mixture of graphite activated carbon, and sodium chloride solution is prepared and mixed with it, discharge reaction and activated carbon regeneration are carried out. The recovery of the electrolyte and the reuse of discharge powder are achieved through mechanical compaction and screening to form a green circulation system.
It effectively avoids water pollution, simplifies equipment, improves discharge rate and safety, realizes efficient recycling of electrolyte and reuse of discharge powder, and is suitable for large-scale use.
Smart Images

Figure CN112382801B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste battery recycling, and in particular to a method for pre-processing waste batteries. Background Art
[0002] As my country's power battery mass retirement is approaching, if the retired power batteries are not properly handled, the threat to the environment is very huge. Power battery recycling has always been an important task related to the green development of the industry, and it is of great significance to resource circulation, green environmental protection, safety management, and industrial development.
[0003] It is generally believed in the industry that battery recycling can be divided into two major directions: cascade utilization and resource recycling. Resource recycling includes discharge treatment, disassembly and crushing, electrolyte recovery, component screening and separation, and wet / pyrometallurgy. At the current stage, the technical level has accumulated relatively mature technology in the wet / pyrometallurgy direction of battery recycling and has achieved industrial application; disassembly and crushing, component sorting, with the gradual improvement of equipment, technical indicators are also getting better and better; however, at this stage, most of the discharge treatment and electrolyte recovery are still in the early stages of research.
[0004] Most companies and enterprises still use the salt water immersion discharge treatment for battery discharge treatment three years ago. This method initially achieved good experimental results and technical indicators in the process of treating small batteries such as lead-zinc, nickel-cadmium, and nickel-metal hydride, and has been widely used due to its simple process, easy operation, and large processing capacity. However, this method also has fatal defects, such as: chlorine and other toxic gases are easily produced during the production process, which is harmful to the human body; it is highly corrosive to the equipment itself, reducing the service life of the equipment; for aluminum-shell batteries, the hydrolysis of aluminum is accelerated during the treatment process, generating foamy or cotton-like precipitation such as aluminum hydroxide and sodium aluminate, which pollutes the water body. For the recovery of electrolyte, the battery is first crushed and then heated, evaporated, and condensed as a whole for recovery. The recovery rate of electrolyte in this method can reach 65%~85%, but because the whole set of equipment is complex and requires a lot of energy consumption, it has not been widely used. Therefore, the pre-treatment process of the entire waste battery needs further technical improvement in the discharge treatment and electrolyte recovery stages. Summary of the invention
[0005] The present invention aims to provide a method for pre-treatment of waste batteries to solve the technical problem of water pollution that cannot be avoided by conventional salt water discharge methods in the prior art.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for pre-treatment of waste batteries is provided. The method comprises the following steps: preparing discharge powder, preparing graphite and activated carbon into a graphite activated carbon mixture, preparing sodium chloride solution, mixing the sodium chloride solution with the graphite activated carbon mixture and stirring it into a wet and loose powder, namely the discharge powder; stacking the discharge powder and the waste batteries to be treated in a layer of discharge powder and a layer of waste batteries to be treated, and mechanically compacting them in a discharge device to carry out a discharge reaction and regeneration of activated carbon; and crushing the waste batteries after discharge together with the discharge powder, mixing and placing them to achieve full adsorption of the electrolyte of the waste batteries by the activated carbon, and then screening, and recovering the obtained discharge powder for reuse.
[0007] Furthermore, graphite and activated carbon are prepared into a graphite-activated carbon mixture in a mass ratio of 1 to 2:1.
[0008] Furthermore, the mass concentration of the sodium chloride solution is 10% to 20%.
[0009] Furthermore, the sodium chloride solution and the graphite activated carbon mixture are prepared in a mass ratio of (1:5) to (3:10).
[0010] Furthermore, the number of stacked layers is controlled to be 2 to 3 layers, and the thickness of each layer of discharge powder is maintained at 20 to 30 cm.
[0011] Furthermore, the temperature of the discharge reaction is 40-80°C.
[0012] Furthermore, an exhaust gas collecting cover is provided above the discharge device.
[0013] Furthermore, the current intensity of the discharge reaction is 1~3A.
[0014] Furthermore, the pH value of the discharged powder is adjusted to 4-5 with oxalic acid or acetic acid.
[0015] Furthermore, the discharge time of the used battery is controlled to be more than 10 hours, and the battery back voltage does not exceed 0.1V.
[0016] The method for pre-treatment of waste batteries of the present invention enables mainstream batteries (especially aluminum shell batteries) at this stage to have a better batch discharge treatment mode. The present invention makes technical improvements to the graphite discharge system. The graphite powder doped with sodium chloride solution enhances the conductivity of the discharge medium. Appropriate moisture reduces the looseness of the medium, accelerates the discharge rate and prevents the generation of graphite dust. It can also enhance the flame retardant effect of the discharge medium and improve safety. The activated carbon is used as the medium to realize the recovery and transfer of the electrolyte, simplifying the production equipment. The multi-component doped graphite discharge technology and the electrochemical regeneration method for regenerating activated carbon technology are used to interconnect the discharge and electrolyte recovery steps to form a set of green circulation system suitable for large-scale use. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 A schematic flow chart of a method for pre-processing waste batteries according to an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] In response to the technical problems described in the background technology, the present invention proposes the following technical solutions.
[0021] According to a typical embodiment of the present invention, a method for pre-processing waste batteries is provided. Figure 1 As shown, the method comprises the following steps: preparing discharge powder, preparing graphite and activated carbon into a graphite-activated carbon mixture, preparing sodium chloride solution, mixing the sodium chloride solution with the graphite-activated carbon mixture and stirring it into a wet and loose powder, namely the discharge powder; stacking the discharge powder and the waste batteries to be treated in a layer of discharge powder and a layer of waste batteries to be treated, and mechanically compacting them in a discharge device to carry out a discharge reaction and regeneration of activated carbon; and crushing the waste batteries after discharge together with the discharge powder, mixing and placing them to achieve full adsorption of the electrolyte of the waste batteries by the activated carbon, and then screening and recovering the obtained discharge powder for reuse.
[0022] The method for pre-treatment of waste batteries of the present invention enables mainstream batteries (especially aluminum shell batteries) at this stage to have a better batch discharge treatment mode. The present invention makes technical improvements to the graphite discharge system. The graphite powder doped with sodium chloride solution enhances the conductivity of the discharge medium. Appropriate moisture reduces the looseness of the medium, accelerates the discharge rate and prevents the generation of graphite dust, and can also enhance the flame retardant effect of the discharge medium and improve safety. The activated carbon is used as the medium to realize the recovery and transfer of the electrolyte, which improves the air pollution caused by the volatilization of the electrolyte during the crushing of the waste batteries, simplifies the production equipment, and utilizes the multi-component doped graphite discharge technology and the electrochemical regeneration method to regenerate the activated carbon technology so that the discharge and electrolyte recovery steps are interconnected to form a set of green circulation system suitable for large-scale use.
[0023] Preferably, the graphite and activated carbon are prepared into a graphite activated carbon mixture at a mass ratio of 1 to 2:1; the mass concentration of the sodium chloride solution is 10% to 20%; the sodium chloride solution and the graphite activated carbon mixture are prepared at a mass ratio of (1:5) to (3:10); the number of stacked layers is controlled to be 2 to 3 layers, and the thickness of each layer of discharge powder is maintained at 20 to 30 cm. Appropriate temperature will accelerate the discharge reaction, and preferably, the temperature of the discharge reaction is 50 to 70°C.
[0024] In the technical solution of the present invention, due to the presence of sodium chloride electrolyte, there will be local electrolytic reaction in the whole discharge process, CI2 and HCIO are generated in the whole system, and the whole discharge powder is weakly acidic with the participation of water; the pH value is appropriately adjusted to 4-5 with weak acids such as oxalic acid and acetic acid, and the activated carbon adsorbed with electrolyte undergoes electrochemical reaction, and the organic electrolyte gradually migrates from the inside to the surface of the activated carbon, and under the action of an external electric field, the organic matter undergoes oxidation reaction with strong oxidants such as CI2 and HCIO on the polarized particles to generate nitroso compounds; in an acidic medium, it is converted into primary amine salts, thereby realizing the regeneration of the activated carbon.
[0025] Preferably, an exhaust gas collection cover is provided above the discharge device to facilitate the recovery of volatilized electrolyte, thereby improving the air pollution caused by the volatilization of electrolyte during the crushing of waste batteries.
[0026] In one embodiment of the present invention, the measured discharge current average is about 2.5A. At this current intensity, sodium chloride concentration of 10% to 20%, and pH value of 4 to 5, the activated carbon achieves the best regeneration effect. The regeneration efficiency of the activated carbon is calculated as follows: 2 LNF concentrated water is measured in a beaker, 5 g of regenerated activated carbon is added, and stirred on a magnetic stirrer for 48 h. The saturated adsorption capacity of the regenerated activated carbon is measured, and the regeneration rate is calculated according to the formula η=(m0-m1) / m0×100%. Where: η——regeneration rate, %; m0——saturated adsorption capacity of new activated carbon, mg / g; m1——saturated adsorption capacity of regenerated activated carbon, mg / g. The first activated carbon regeneration rate reaches more than 95%, and after three cycles, the activated carbon regeneration rate can still reach more than 85%; in order to ensure the best discharge effect and the battery does not return to pressure after discharge, the battery needs to be further deeply discharged, and the deep discharge time is controlled to be more than 10 hours. At this time, the battery back pressure does not exceed 0.1V, which is much higher than the requirement of 1.0V discharge cut-off voltage for safe crushing.
[0027] In one embodiment of the present invention, the discharged battery and the discharged powder are coarsely crushed and cut together to minimize the volatilization of the internal electrolyte during the process. The components containing the electrolyte are evenly mixed with the discharged powder and placed for 10 to 30 hours to achieve sufficient adsorption of the electrolyte by the activated carbon. After screening and separation, the discharged powder continues to be used in conjunction with the next discharged battery.
[0028] In one embodiment of the present invention, after three cycles, a large amount of sodium chloride is lost in the discharge powder, and the regeneration rate of the activated carbon is greatly reduced due to interference from various impurities. It is necessary to use deionized water to wash and soak to remove excess impurities and salts, and reconfigure and use after high-temperature drying to achieve the best effect. The graphite used in the present invention is not limited to natural graphite or artificial graphite with strong conductivity, and the activated carbon used is not limited to granular and columnar activated carbon such as coconut shell carbon and wood carbon.
[0029] The beneficial effects of the present invention will be further described below in conjunction with embodiments. Example 1
[0030] A retired cylindrical lithium iron phosphate battery with a voltage of 3.255V and a rated capacity of 5Ah is placed in a device with an exhaust gas collection hood, and the collection hood is connected to the exhaust gas treatment device. The discharge powder is prepared in the following proportions: 10kg of graphite and activated carbon are taken and stirred, 4000ml of water and 600g of sodium chloride solid are prepared into a sodium chloride solution, and the prepared sodium chloride solution is mixed with the mixed graphite activated carbon, and stirred evenly into a wet and loose powder. A layer of 30cm thick discharge powder is spread in the discharge device, and the batteries to be discharged are evenly placed on the discharge powder; after the batteries are placed, a layer of 30cm thick discharge powder is spread on the batteries and compacted, and this operation is repeated to stack three layers of batteries, and the powder is sprayed with oxalic acid solution to adjust the pH value to 4. The discharge time is 2 hours. At this time, the maximum temperature in the discharge powder does not exceed 60 degrees, and the current in the powder gradually decreases from 5A to 0A. Then the battery needs to be placed in the powder for 10 hours for deep discharge; then the battery is taken out for measurement, and the battery voltage is stable at 0V. The discharged battery and the discharge powder are sent to the coarse crusher together, and the battery is crushed into particles with a particle size of 2cm. Then, after mixing with the discharge powder for 24 hours, the activated carbon fully adsorbs the electrolyte and is screened with a 0.4cm screen. The battery crushed material is on the screen, and the powder adsorbed with the electrolyte is on the screen. After removing the electrolyte, the battery crushed material enters the fine crushing system for the next stage of processing, and the powder returns to the discharge device to participate in the discharge of the next batch of batteries. After 3 cycles, the discharge powder is stirred and washed with 1 cubic meter of deionized water for 1 hour to remove residual organic matter and salt, and then rinsed with 1 cubic meter of deionized water. After the powder is filtered and dried at 600℃, the sodium chloride solution and the lost graphite and activated carbon are replenished in proportion. The loss rate of graphite and activated carbon in three cycles is about 10%. The discharged powder after replenishment is returned to the system for use. Example 2
[0031] Place retired ternary nickel-cobalt-manganese square batteries with a voltage of 4.255V and a rated capacity of 60Ah in a device with an exhaust gas collection hood, which is connected to an exhaust gas treatment device. Prepare the discharge powder in the following proportions: take 20kg of graphite and 10kg of activated carbon and stir them evenly, take 9000ml of water and 1800g of sodium chloride solid to prepare a sodium chloride solution with a solid-liquid ratio of 1:5, mix the prepared sodium chloride solution with the mixed graphite activated carbon, and stir evenly to form a wet and loose powder. Spread a 30cm thick layer of discharge powder in the discharge device, and place the battery to be discharged flat on the discharge powder; after the battery is placed, spread a 30cm thick layer of discharge powder on the battery and compact it, repeat this operation to stack three layers of batteries, spray the powder with acetic acid solution, and adjust the pH value to 5. The discharge time is 24 hours, the maximum temperature in the discharge powder does not exceed 60 degrees, and the current in the powder gradually decreases from 5A to 0A. Then the battery needs to be further deeply discharged for 10 hours, and then the battery is taken out for measurement. At this time, the battery voltage is stable at 0V. The discharged battery is cut to remove the pole piece, and a layer of discharge powder is laid flat on the west side of the cutting platform to receive the outflowing electrolyte. The pole piece taken out is mixed with the discharge powder and placed for 6 hours. The discharge powder and the pole piece are separated by sieving with a 2mm sieve, and the powder is returned to the discharge device to participate in the discharge of the next batch of batteries. After 3 cycles, the discharge powder is stirred and washed with 1 cubic meter of clean water for 1 hour to remove residual organic matter and salt. After filtration, it is dried at 600℃, and the sodium chloride solution and the lost graphite and activated carbon are replenished in proportion. The loss rate of graphite and activated carbon in three cycles is about 3%. The replenished discharge powder is returned to the system for use.
[0032] The above embodiments achieve at least the following technical effects:
[0033] 1. Avoid water pollution caused by conventional salt water discharge method;
[0034] 2. It can realize large-scale processing with high efficiency;
[0035] 3. The auxiliary materials used can be recycled and reused, and the production process is green and environmentally friendly;
[0036] 4. Suitable for most types of batteries, including aluminum, steel shells, square, cylindrical and other batteries.
[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for pre-treatment of waste batteries, characterized in that: The following steps are involved: Prepare discharge powder, prepare graphite and activated carbon into a graphite activated carbon mixture, prepare sodium chloride solution, mix the sodium chloride solution and the graphite activated carbon mixture and stir them into a wet and loose powder, which is the discharge powder; The discharge powder and the waste batteries to be processed are stacked flatly in a layer of the discharge powder and a layer of the waste batteries to be processed and mechanically compacted in a discharge device to carry out a discharge reaction and regeneration of the activated carbon; as well as The waste batteries after discharge are crushed together with the discharge powder, mixed and placed to enable the activated carbon to fully adsorb the electrolyte of the waste batteries, and then screened and the obtained discharge powder is recovered for reuse.
2. The method according to claim 1, characterized in that The graphite and the activated carbon are prepared into the graphite-activated carbon mixture in a mass ratio of 1-2:
1.
3. The method according to claim 2, characterized in that The mass concentration of the sodium chloride solution is 10% to 20%.
4. The method according to claim 3, characterized in that The sodium chloride solution and the graphite activated carbon mixture are prepared in a mass ratio of (1:5) to (3:10).
5. The method according to claim 1, characterized in that: The number of stacked layers is controlled to be 2-3 layers, and the thickness of each layer of the discharge powder is maintained at 20-30 cm.
6. The method according to claim 1, characterized in that The temperature of the discharge reaction is 40-80°C.
7. The method according to claim 1, characterized in that A tail gas collecting cover is arranged above the discharge device.
8. The method according to claim 1, characterized in that The current intensity of the discharge reaction is 1~3A.
9. The method according to claim 1, characterized in that: The pH value of the discharge powder is adjusted to 4-5 by using oxalic acid or acetic acid.
10. The method according to claim 1, characterized in that The discharge time of the waste battery is controlled to be more than 10 hours, and the battery back voltage does not exceed 0.1V.